Contraction force versus action potential duration of cardiomyocytes: which methodology is more informative for selection of effective 1,4-dihydropyridine compounds in experimental research? - Barsys, Vygantas; Garalienė, Vida; Urbonas, Gediminas (Acta medica Lituanica, 2015)
Background. Identification of activity properties of new synthesized compounds is important to help choose the adequate research methodology. The goal of this experimental research was to determine the relationship between the chemical structure of 25 compounds of 1,4-dihydropyridine derivatives and their effects on the contraction force of guinea pig papillary muscles and the action potential (AP) duration. Methods. AP recordings were obtained with standard microelectrodes that were made from borosilicate glass capillaries, filled with 2.5 M KCl and connected to the high-input impedance amplification system. 1.0 Hz stimulation frequency was used. The contraction of papillary muscles was recorded by using a force transducer. Both signals (inotropic response and AP) were digitised by an A/D converter and registered by a computer specialised program. Results. The results have shown that most of 1,4-dihydropyridine derivatives possessed the negative inotropic action and had the negligible impact on the AP duration. It was identified that 1,4-dihydropyridine compound OSI 9719 (2-propoxyethyl-4-difloemethoxyphenyl-2-methyl-5-nitro-1,4-dihydropyridine-3carboxylate) had a prolonged duration of AP and simultaneously increased the force of contraction (p